A methodology for identification of damage in beams - Barbieri N. (2016)
© 2015 Taylor & Francis.In this work, a parameter based on correlation of signals using mathematical morphology and other two parameters based on energy of a vibration signal using wavelet transform and bispectrum theory are used for approximate location of damage in a steel clamped-free beam. The experimental data are obtained through accelerometers placed along the sample. The system is excited using impact hammer. A preliminary location of the damage is found using the position of the accelerometer that has a higher energy change when it is compared to the signal of the system with and without damage. The mathematical models are obtained using 2D elasticity theory and the finite element method. The numerical and experimental data are approximated using the particle swarm optimization method, and this way, it is possible to adjust the location and severity of the damage. The procedure is also applied to a free–free steel beam with two damages and a sandwich beam.